Labor Migration Trend in Nepal (The Geographic Base, 2021)
Migration is one of the major factors affecting population distribution of Nepal. Job opportunity, education facility, medical facility and topographic situation are the key causes of migration. Human movement from mountain to hill; hill to Tarai; and rural to urban area migration are the major trend observed in Nepal. Migration has direct impact on various sectors including financial, social, demographic, and biological. All kind of services including educational, medical, transformational, and safety services should make equally accessible over the various parts of the country. This research helps to understand the trend of internal and international labor migration in Nepal. The study has used secondary data from Department of Foreign Employment (DoFE), Central Bureau of Statistics (CBS), Ministry of Finance (MoF). Remittance is playing a crucial role in the Nepalese economy. The highest foreign labor migration was found in the year 2013/14. The trend was continuously increased until 2013/14 and it has stated decreasing thereafter. International labor migration has mostly taken place to Malaysia, Qatar, Saudi Arabia, 110 UAE and other Southeast Asian countries and it is growing over the time that has shifted the agricultural based economy towards remittance-based economy.